Alzhiemer mystery and Y chromosome - NEHA GUPTA; VARUN JAISWAL (International Journal of Pharma and Bio Sciences, 2017)
Alzheimer Disease (AD) is a neurodegenerative disorder with unknown etiology even after 110 years of its discovery. Etiology of AD is different in male and female and female brain is more susceptible to AD but underlying molecular mechanism is unknown. Current study aims to find Y chromosome genes associated with AD incidence. Analysis of genes differentially expressed in male and female AD samples may be helpful to identify causes of AD etiology. Genes encoding cell adhesion molecules, protocadherin (PCDH11Y) and neuroligin (NLGN4Y), were found to be involved in AD. Beside protein coding genes, antisense RNA and pseudogene were also differentially expressed. This is the first study focusing Y chromosome transcriptome in context to the AD disease. Differentially expressed genes were suggested to be associated with AD in previous studies justifies the current approach. These genes if explored more will aid in understanding of AD and design better therapeutics.